Estudio de viabilidad para el ahorro energético y mejora del consumo eléctrico de la fábrica ORANGINE durante el año 2015. - Calero Calero, Andrés Sebastián (2016)
When talking about energy efficiency, directly the topic about saving energy is taken. The country has promoted since a long time ago some strategies and tactics to improve the energy resource consume to benefit Ecuador and cares the environment. In the project, is showed how the reality nowadays at ORANGINE factory is in the first semester of 2015 in consume of its energy resources and as conclusion the biggest energy consumer that produce the highest economy expense is the electricity. The project was made in the Crown line production with the study of solid diagrams. There were evaluated some factors that damage the electrical consume with a three phase power quality analyzer, as result the voltage spikes generated by the continuous random starters in the engines (DIP’s events) are the main problem that produce the biggest electrical consume. That’s why; in the technical document one suggestion is the technical improvement with soft starters and high efficiency engines to decrease the electric power. In the area of the finished product warehouse a study was made for the lighting system. It has to work with the levels of lighting given by lumen method and also by the Decreto Ejecutivo 2393: Art 56. “Iluminación, Niveles Mínimos”, and ensures a good job area for the personal. At the end of the analysis, as conclusion, if the factory doesn’t improve its old engines, doesn’t get slow starters and doesn’t have a high tech lighting system, it wouldn’t save 11,236.48 USD per year.